First Report of Pythium aphanidermatum causing crown and root rot in Cannabis sativa (L.) in Florida - Blit, Eden S; Philbrook, Richard N; Indest, Matthew; Perez-Martinez, Jose; Palozzo, Dominick; Warren, Jeremy (Plant disease, 2025)
In October of 2023, Cannabis sativa (L.) cuttings of three different cultivars grown in rockwool at an indoor facility (1988 m2; 1300 plants) in Mt. Dora, FL were observed with brown, water-soaked stems that failed to form roots. Three symptomatic clones of each affected cultivar were selected for pathogen identification. In a laminar flow hood, their stems were surface sterilized in 1% sodium hypochlorite for 2 minutes, rinsed in sterile deionized (DI) water, and cut into 1cm segments with a heat-sterilized scalpel. The segments were embedded in water agar (WA) and incubated in darkness for 48 hours at 27oC. Hyaline filaments growing from the stem segments were subcultured onto V8 agar and PDA, then incubated for 48 hours. On V8, fast-growing mycelium grew from the stem of cultivar "PBR". The culture was white and had cottony aerial mycelium. On PDA (Figure 1A), the mycelium produced a radial pattern with aseptate filaments, consistent with Pythium spp. morphology (Chen Y.-A., et al. 2024). DNA was extracted from mycelium using Quick DNA Fungi/Bacterial Kit (Zymo Research Irvine, CA, USA). PCR was performed using ribosomal ITS primers ITS100/ITS4 (Riit et al. 2016), amplifying oomycete rDNA of Internal Transcribed Spacer regions. A second PCR was performed using COI primers OomCox-Levup/OomCox-Levlo, amplifying cytochrome oxidase subunit 1 (COI) (Robideau et al. 2011). Amplicons were Sanger sequenced, trimmed, and aligned using SnapGene software, and compared to known sequences using BLAST. Amplicons showed 100% identity to Pythium aphanidermatum accessions KX260336 (775bp/775bp) and 99.21% identity to AY129164 (1299bp/1299bp). Consensus sequences were deposited in GenBank with accessions OR731869 (ITS) and PP806568 (COI). A phylogenetic tree was constructed with MEGA software, illustrating the evolutionary relationships between the P. aphanidermatum isolate and other Pythium/Globisporangium species based on concatenated ITS and COI sequences (Figure 2). A 3 day old pure culture of P. aphanidermatum was diced and transferred to 250mL of V8 broth; a negative control was prepared using sterile V8 media. The broths were placed on a rotary shaker and incubated for 48 hours at 30oC and 100 rpm. Light microscopy revealed filamentous growth and motile zoospores in the inoculated suspension, and no growth in the negative control. To test Koch's postulate, 30 rockwool cubes (150cm3) were soaked in the broths: 15 in the inoculated, 15 in the control. The stems of 30 unrooted "PBR" C. sativa cuttings were dipped in rooting gel (Clonex Rooting Gel, Growth Technology, Somerset, UK) and embedded into each rockwool cube. Cuttings were grown indoors, at 27°C for 14 days under LED lights with an 18-hour photoperiod. Inoculated cuttings displayed brown, water-soaked stems and failed to root (Figure 1B); control cuttings were asymptomatic and successfully rooted. Stem samples from 2 infected and 2 control cuttings were plated as previously described. After 48 hours at 27C, mycelial growth was observed from stems of infected plants but not from controls; hyphal transfers were re-plated on PDA. DNA extraction and PCR amplification for ITS and COI amplicons were performed from the cultures, Sanger sequenced and aligned with the previous sequences. All ITS and COI sequences were identical to the original sequences from infected plants. Pythium spp. have a wide host range and Cannabis is no exception (Thiessen & Troth, 2019). Since most Cannabis cultivators rely on clonal cuttings to populate grows, P. aphanidermatum infection hinders production and harvest yield maximization, causing economic damages.